Determining the Effects of High-Intensity Interval Training Versus Plyometric Training on Speed, Agility, and Lower-Limb Explosive Performance in Male Basketball Players - Tulsidas, Udaipuram; Albert Chandrasekar, Sigamani Jayasingh; Shankar, Chella Mittinti; Velukuri, Kiran; Ahamed, Reyash Ajmal; Venugopal, Senthil; Kaur, Dilpreet; Kambitta Valappil, Ibnu Noufal; Karmakar, Debajit; Boby, Farjana Akter; Astuti, Yuni; Salvi, Nirmal Michael (Physical Education Theory and Methodology, 2025)
Background. High-Intensity Interval Training (HIIT) and Plyometric Training (PT) are commonly used to enhance athletic performance in sports requiring speed, agility, and explosive lower-limb power, such as basketball. While both methods improve neuromuscular and physiological capacities, their comparative effectiveness on specific motor abilities remains unclear. Objectives. This study aimed to evaluate and compare the effects of HIIT and PT on speed, agility, and lower-limb explosive performance in male basketball players. Materials and methods. A total of 22 male basketball players (overall age; 21.27 ± 1.34 years) were randomly assigned to two intervention groups: High-Intensity Interval Training (HIIT, n = 8) and Plyometric Training (PT, n = 14). Both groups underwent their respective training programs over a specified intervention period. Key performance variables, including speed, agility, squat jump (SJ), and countermovement jump (CMJ), were assessed before and after the training. A two-way repeated measures ANOVA (2 × 2) was employed to evaluate the interaction effects between time (pre- and post-intervention) and group (HIIT vs. PT) on all outcome measures. Results. Both the HIIT and PT groups showed significant improvements in sprint time, agility, jump height, velocity, power, and power-to-bodyweight ratio (all p < .001). No marked changes were found in SJ force. A two-way ANOVA revealed a significant time effect for all variables (p < .001), with no substantial group or interaction effects (p > .05), indicating comparable improvements across both interventions. Conclusions. These findings confirmed that both High-Intensity Interval Training and Plyometric Training were effective in enhancing speed, agility, and lower-limb explosive performance among male basketball players. The absence of significant differences between groups suggests that either training method can be effectively incorporated into performance enhancement programs based on athlete preference, training context, or resource availability.